The Smart Culture, Smart Governance Integrating Digitalization and Local Wisdom In The Bureaucratic Reform of Pleret Village, Bantul, Yogyakarta - Karlina Setyawati; Sri Widayanti (Journal of Indonesian Rural and Regional Government, 2025)
This study explores the transformation of village bureaucracy towards governance that is adaptive to the digital era, emphasizing the integration of digitalization and local wisdom in Pleret Village, Pleret District, Bantul Regency. A descriptive qualitative approach was applied using in depth interviews, participatory observation, and document analysis. The findings show that the digitization of public services through village applications, online budget transparency, and the strengthening of culture based community participation have improved accountability, responsiveness, and bureaucratic efficiency. However, challenges remain in terms of digital literacy among residents and uneven access to technology. Integrating local cultural values such as deliberation, mutual cooperation, and traditional social institutions are key to the sustainability of bureaucratic reform. This study recommends strengthening the digital capacity of both village officials and residents, as well as developing culturally grounded policies to support sustainable village governance.